Potential Intensive Care unit Ventilator Demand/Capacity Mismatch due to Novel Swine-Origin H1N1 in Canada - Paul Smetanin; David Stiff; Anand Kumar; Paul Kobak; Ryan Zarychanski; Neil Simonsen; Frank Plummer (Canadian Journal of Infectious Diseases and Medical Microbiology)
PURPOSE: To investigate the ability of Canadian intensive care units (ICUs) and ventilators to handle widespread re-emergence of the swine-origin H1N1 virus in the context of an aggressive strategy of vaccination.